The Implementation of the Tikrar Method in Quran Memorization Learning at Raudhatul Hasanah in Mulyorejo - Latifah, Dina; Holid, Syahrul (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the planning, implementation, success rate, and challenges in applying the Tikrar method to Qur'an memorization learning at the Tahfidzul Quran Raudhatul Hasanah Foundation. This research employed a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation. The results indicate that: (1) learning planning is systematically carried out through the preparation of memorization schedules, achievement targets, and supporting facilities; (2) the implementation of the Tikrar method involves intensive repetition of verses, regular memorization submissions, and close guidance from tahfidz teachers; (3) the application of this method shows a high level of success in improving fluency, memory retention, and building students' confidence in recitation; and (4) challenges such as student fatigue, varying levels of memorization ability, limited time, and low parental involvement still persist but can be addressed through motivation reinforcement strategies and supportive learning environments. Thus, the Tikrar method remains an effective and relevant approach to sustainably improving the quality of Qur'anic memorization among students.